RELIGIOUS EDUCATION AND ADOLESCENT RELIGIOSITY (Part 1: Urban and Rural Madrasah Aliyah Characteristics in Lombok Island) - Mira Mareta (Jurnal Tatsqif, 2021)
The current social circumstances at the spiritual level have brought an enormous influence on the establishment of religious behavior in adolescent students, both in the level of belief, practice, and religious experience. Religious education in the madrasah environment has a strategic position in building students' religious behavior. This study aims to explain why the rural and urban madrasah environment context is essential to observe the role of religious education, especially Islamic education, in building students' religious behavior in Lombok island. Then it sorts out the madrasahs characteristics or uniqueness from the two different regions, rural and urban. This research is qualitative psychological research with ecological contextual theory as the theoretical framework. The data analysis method is descriptive and holistic by employing three flows of interacting activities, e.g., reducing data, presenting it, and drawing conclusions. Data was obtained through documentation, observation, and in-depth interviews. This research was conducted in six madrasahs, i.e., two Madrasah Aliyah located in the downtown, and four Madrasah Aliyah, which geographically represent the category of the rural madrasah. The research results indicate that the spiritual development of the students cannot be separated from the religious education context in their environment. In urban areas context, the madrasah environment has formal systemic characteristics, is supported by strong management and leadership, maintains the madrasah stability and conduciveness by implementing a power strategy through a set of rules and code of conduct. Meanwhile, madrasas in rural areas have flexible, dynamic, and adaptive characteristics, in which education takes into account cultural aspects and values applied in the community.